(untitled) (International journal of artificial intelligence, 2025)
This article analyzes the dynamics of the increase in crimes committed using information technologies, the threats they pose to the security of society and the state, as well as the state policy and legal reforms implemented in Uzbekistan to counter such crimes. In particular, it examines the new institutional and legal mechanisms for combating cybercrime, developed based on the Presidential Decree No. ПҚ–153 dated April 30, 2025, the activities of authorized bodies, preventive measures, the responsibility of the banking and financial sector, and accountability measures. The article also offers specific recommendations for preventing these crimes and improving the legal framework.